Selected psychological determinants of sports results in senior fencers - Tomczak, M.; Walczak, M.; Breczewski, G,. (Human Movement, 2012)
The aim of the present study was to determine the correlations between the strength of the stimulation process, mobility of nervous processes, achievement motivation and sports results of fencers in the senior age category. Methods. The sample was comprised of 38 senior fencers (19 men and 19 women) aged 21-32 years. The strength of the stimulation process and mobility of nervous processes were assessed with the Strelau and Zawadzki PTS inventory. The subjects' achievement motivation was measured with the achievement motivation questionnaire by Widerszal-B azyl. Results. The study revealed that senior fencers (women, in particular) featured higher mean levels of the examined psychological determinants, i.e., strength of the stimulation process, mobility of nervous processes and achievement motivation than the general population in the same age range. Strong and statistically significant correlations were found between all the studied psychological determinants and sports results among the male fencers in the sample. In the group of female fencers none of the correlations were statistically significant. Conclusions. The results might provoke reflection on the role of coaches and, consequently, may have implications for the cooperation between coaches and athletes, indicating that the individual psychological differences of fencers should be considered during training. The coach may also decide on the necessity for considering on the reported diversification within the gender or age domain, and the need to consider such psychological properties as temperamental characteristics or the level of achievement motivation.